Inovasi Operasional untuk Efisiensi Biaya dan Peningkatan Profit di Industri Pengolahan Limbah Plastik - Marlina, Marlina; Sufitrayati, Sufitrayati; Amri, Saiful; Syamsuddin, Nurfiani; Radhiana, Radhiana; Maulana Akbar, Rian (Jurnal Serambi Engineering, 2025)
This study explores operational innovation as a strategic solution for cost efficiency and profit improvement in the plastic waste processing industry. The research aims to identify effective strategies and methods for operational optimization while addressing key challenges such as high production costs, global competition, and environmental sustainability. The methodology involves a qualitative approach with case studies and literature analysis to examine the application of smart technologies, lean manufacturing, and circular economy principles. Findings highlight significant cost reductions, enhanced operational efficiency, and strengthened competitive advantage. The study contributes to the development of sustainable practices and innovation-driven growth for the plastic waste processing sector.